Verlängerte Praxisphasen in der Lehrer*innenbildung Konzeptionelle und empirische Aspekte der Relationierung von Theorie und Praxis - Rheinländer, Kathrin; Scholl, Daniel (Verlag Julius Klinkhardt, 2020)
School-based practical courses have become an integral part of teacher training, both nationally and internationally. Although the expectations of these components are high and research activities in this area have increased in recent years, there is still a need for clarification on the question of the extent to which practical school study components actually fulfil the functions of professional orientation, competence development and theory-practice relation attributed to them. With this volume, the Centre for Teacher Education at the University of Vechta would therefore like to make a contribution to expanding the existing research situation, especially with regard to the relational function of theory and practice in extended practical phases. The contributions range from conceptual to empirical aspects of this function.